Muscle and Joint Factors Associated With Forefoot Deformity in the Diabetic Neuropathic Foot - Cheuy, Victor A. (Foot Ankle Int, 2015)
BACKGROUND: Diabetic forefoot joint deformities are a known risk factor for skin breakdown and amputation, but the causes of deformity are not well understood. The purposes of this study were to determine the effects of intrinsic foot muscle deterioration and limited ankle joint mobility on the severity of metatarsophalangeal joint (MTPJ) deformity, and determine the relationships between these potential contributing factors and indicators of diabetic complications (peripheral neuropathy and advanced glycation end products). METHODS: A total of 34 participants with diabetic neuropathy (average age, 59 years; range 41-73) were studied. MTPJ angle and intrinsic foot muscle deterioration were measured with computed tomography and magnetic resonance imaging, respectively. Maximum ankle dorsiflexion was measured using kinematics. Skin intrinsic fluorescence served as a proxy measure for advanced glycation end product accumulation. RESULTS: Total forefoot lean muscle volume (r = −0.52, P < .01) and maximum ankle dorsiflexion (r = −0.42, P < .05) were correlated with severity of MTPJ deformity. Together they explained 35% of the variance of MTPJ angle. Neuropathy was correlated with forefoot muscle deterioration (ρ = 0.53, P < .01). Skin intrinsic fluorescence was correlated to severity of neuropathy (r = 0.50, P < .01) but not maximum ankle dorsiflexion, or forefoot deterioration when controlling for neuropathy. CONCLUSION: These results suggest that the interplay of intrinsic foot muscle deterioration and limited ankle mobility may be the primary contributor to the development of MTPJ deformity. Identifying these muscle and ankle motion impairments as risk factors for MTPJ deformity supports the need for targeted interventions early in the disease process to slow, or possibly stop the progression of deformity over time and reduce the risk of amputation. LEVEL OF EVIDENCE: Level IV, case series.